CONFERENCE OF YOUNG SCIENTISTS - article editorial (Педиатрическая фармакология, 2008)
A conference of young scientists dedicated to the 245th anniversary of the Scientific Center of Children's Health was held on September 12, 2008.Speakers at the conference were young professionals working at SCCH of RAMS, Sechenov Moscow Medical Academy, Institute of Pediatric Hematology, Oncology, and Immunology. During the conference the poster session was held in which young scientists of the Centre took part. Presentations of participants were evaluated by the members of the Academic Council of SCCH, leading specialists of the Center. Gifts to the winners of the conference were provided by "Procter & Gamble".Winners and awardees:I place: Chistyakova V.P. - Clinical intern at SCCH of RAMS;II place: Gudkova E.Yu. - Researcher at the Department of Rheumatology of SCCH of RAMS;III place: Darmanyan A.S. - Researcher at the Department of diagnostics and rehabilitation treatment of SCCH of RAMS.Best poster paper: Plyakin V.A. - Researcher at Surgical Department NTSZD RAMS.Audience Award: Tikhomirova E.A. - Researcher at the Department of functional diagnostics of SCCH of RAMS.